Determinants of trading volume in real estate investment trusts / Hairulnizam Hashim - Hashim, Hairulnizam (Institute of Graduate Studies, UiTM, 2013)
Real estate investment trusts (REITs) show lower average volumes than similar non-REITs. Lower average volume is among the main reason of institutional investors’ disinterest to invest in REITs. Consequently, the lower participation of institutional investors causes the lower return performance of REITs. There are very limited studies on trading volume in REITs. Most of the studies focus on examining the level of trading volume. In reviewing past studies which regard to variables that have significant relationship with trading volume of non- REITs, only proxies for stock market data have been used. This indicate the need to examine other important variables such as macro-economic data, type of returns, firm size, market structure and period effect in modelling determinants that affect trading volume of REITs. In filling the gap of the previous works, this study had also tested whether variables that have significant relationship and significantly related to trading volume in non-REITs market, will also affect significantly the trading volume of REITs. The variables identified are price return, absolute price return, volatility, dividend yield, percentage change of long-term interest rate, absolute percentage change of long-term interest rate, firm size, year of trading, type of return, trading volume (lag one) and trading volume (lag two)…